Effect of torsion in long-baseline neutrino oscillation experiments - Papia Panda; Dinesh Kumar Singha; Monojit Ghosh; Rukmani Mohanta (European Physical Journal C: Particles and Fields)
Abstract In this work, we investigate the effect of curved spacetime on neutrino oscillation. In a curved spacetime, the effect of curvature on fermionic fields is represented by spin connection. The spin connection consists of a non-universal “contorsion” part which is expressed in terms of vector and axial current density of fermions. The contraction of contorsion part with the tetrad fields, which connects the internal flat space metric and the spacetime metric, is called torsion. In a scenario where neutrino travels through background of fermionic matter at ordinary densities in a curved spacetime, the Hamiltonian of neutrino oscillation gets modified by the torsional coupling constants $$λ _{21}^{′ }$$ λ 21 ′ and $$λ _{31}^{′ }$$ λ 31 ′ . The aim of this work is to study the effect of $$λ _{21}^{′ }$$ λ 21 ′ and $$λ _{31}^{′ }$$ λ 31 ′ in DUNE and P2SO. In our study we, (i) discuss the effect of torsional coupling constants on the neutrino oscillation probabilities, (ii) estimate the capability of P2SO and DUNE to put bounds on these parameters and (iii) show how the physics sensitivities get modified in presence of torsion.